TALENT AS A FEATURE OF A RUSSIAN FOLK FAIRY TALE HERO - Grakhova, Svetlana; Belyaeva , Nina; Mustafina, Svetlana; Sharafetdinova, Zemfira; Murzakaeva, Camille (Revista Inclusiones, 2020)
The article is aimed at revealing the sense of a fairy tale that is one of the most popular genres of Russian folk art. A fairy tale reflects the artistic perception of the world, aesthetic and moral ideals, tastes, spiritual culture and talent of the nation. Therefore, it has constantly attracted and is still attracting attention of scientists around the world. Special attention has always been paid to the images of characters that are quite widely and variously presented in a Russian fairy tale. These are main characters and minor ones; magical (mythological) and ordinary characters; characters distinguished by their social status or by the functions performed in a fairy tale, etc. However, the typical and well-known hero has become Ivan endowed with many personal characteristics, abilities, and, most importantly, a kind soul. There are some other heroes such as Emelya, Vasily, Shish, and others. But all of them resemble Ivan, a powerful and symbolic image that has absorbed both mythological, and historical, social ideas of the Russians.